KARAKTERISTIK PRODUK ENERGY CHEWS KULIT BUAH SEMANGKA DENGAN PENAMBAHAN AIR JERUK LEMON - Hasan Priya Atmaja; Zulia Setiyaningrum; Agung Setya Wardana; Nur Lathifah Mardiyati (Fakultas Pertanian Universitas Riau, 2022)
Endurance sports are a type of sports that prioritize continuous endurance for a long time so that it releases energy and sweat that exceeds ordinary activities. Therefore, complementary foods are needed to overcome the loss of energy and fluids during exercise such as energy chews. The addition of lemon was intended to add flavor, a source of potassium and as a natural preservative for the product. The purposes of this study were to describe and analyze the water and potassium contents of the watermelon rind with the addition of lemon zest energy chews. This was a true experimental study using a completely randomized design (CRD) which consists of 4 formulations with the addition of lemon juice; 0 g, 25 g, 30 g and 35 g lemon juice per 50 g watermelon rind. The water content tests used the oven method and the potassium test used the gravimetric method. The results of the water content test got an average value of 80.16% while the results of the potassium level test got an average value of 101.84 mg/100g. The results of the influence test of lemon zest addition on water content showed p value = 0.956 while potassium content p = 0.884. There were no effects of the addition of lemon zest on the water and potassium content of the watermelon rind energy chews product. The water content in energy chews products did not meet the SNI requirements of a maximum of 20% so that it still needs further development.